Proporções de volumoso e concentrado associadas a ofertas hídricas para ovinos confinados - Silva, Claudete Maria da (2014)
The effects of different offers roughage, concentrate and water performance, economic viability, characteristics and carcass yield of sheep were evaluated. We used 40 crossbred sheep de Santa Inês, uncastrated, with an average initial weight of 18.85 ± 2.80 kg and mean age 5.0 ± 2.0 months, distributed in a completely randomized design, on a 2x2 factorial design, consisting of two forage to concentrate ratios: 30:70 and 70:30 with their energy levels: 2.67 and 2.10 Mcal of ME/kg DM and two offerings of water (water ad libitum and restricted by 50%) with 10 replicates during 73 days. To evaluate the characteristics and performance of the carcasses, the animals were slaughtered at an average weight of 27.62 ± 3.06 kg. Proximate composition (% moisture, % ash, % protein and % ether extract) of Longissimus dorsi was determined, and the same was considered the color parameters (L *, a * and b *), shear force, cooking loss and pH. The water restriction caused effect (P<0.05) on dry matter and nutrients, and total daily gain weight regardless of roughage and concentrate. There was no effect (P>0.05) of water restriction on feed conversion and efficiency. The total weight gain, average daily gain, feed conversion and efficiency were influenced by the proportions of forage and concentrate. The evaluation of economic results revealed that all combinations of water supply and levels of dietary energy to produce crossbred sheep de Santa Inês were positive for gross income and profit. Higher total cost of the diet was obtained when the animals were fed with high level of concentrate. There was no effect (P<0.05) of water restriction on the chemical composition, in variations of color (L *, a * and b *), weight and cut yields, and the evaluation parameters for carcass yield, except to the final weight. Weights and carcass were influenced (P<0.05) the proportion of forage and concentrate, no differences in cooling losses and biological yield. There was effect (P<0.05) of restriction of water in cooking loss. It was concluded that, when associated higher proportion of roughage in the diet with water restriction animal performance is reduced and the combination of diet and fluid restriction and concentrate more than 50% of consumption allows higher net income and improved benefit cost ratio. Higher weights and yields of hot and cold carcass are obtained in animals fed diets with a higher share of the concentrate.